2022
DOI: 10.2147/copd.s346294
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Risk of Mortality Associated with Isolation of Pseudomonas aeruginosa in COPD: A Systematic Review and Meta-Analysis

Abstract: Background: Chronic bronchial infection is frequent in chronic obstructive pulmonary disease (COPD), but the impact of the isolation of pathogenic bacteria, and in particular Pseudomonas aeruginosa (PA) in respiratory samples on the prognosis of COPD is unclear. Methods: We conducted a systematic review of prognostic studies including patients with isolation of PA in sputum in stable state or during exacerbations of COPD. The main outcomes were all-cause mortality, respiratory mortality, and number and severit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 42 publications
0
10
0
1
Order By: Relevance
“…During the early stages of COPD, airways are predominantly colonized with H. influenzae, M. catarrhalis, and S. pneumoniae. These bacterial species drive inflammation and tissue damage as previously described ( 111 , 115 117 , 119 121 ). Mechanisms of tissue damage induced by these bacteria are discussed further in the following sections.…”
Section: Airway Bacterial Colonizationmentioning
confidence: 88%
See 2 more Smart Citations
“…During the early stages of COPD, airways are predominantly colonized with H. influenzae, M. catarrhalis, and S. pneumoniae. These bacterial species drive inflammation and tissue damage as previously described ( 111 , 115 117 , 119 121 ). Mechanisms of tissue damage induced by these bacteria are discussed further in the following sections.…”
Section: Airway Bacterial Colonizationmentioning
confidence: 88%
“…These effects are mediated via the release of bacterial outer membrane vesicles harboring extracellular products, such as LPS, a potent inflammatory stimulus demonstrated by earlier studies to induce lung emphysema in hamsters ( 118 ). Several COPD human studies have supported this hypothesis, showing that bacterial colonization of the airways induces inflammation ( 111 , 115 117 , 119 121 ) and impairs lung function (FEV 1 ) ( 122 ).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…The meta-analysis also revealed that individuals with COPD had an adjusted higher death risk when PA separated from sputum. 78 …”
Section: Discussionmentioning
confidence: 99%
“…The isolation of PA in sputum in COPD deserves special attention. Old studies have shown that PA has a role in exacerbations, particularly in more severe COPD patients, 45 and new evidence suggest that PA may be associated with increased mortality in COPD; 46 , 47 all these studies support a role of PA in the progression of the disease. Murphy et al 48 observed that acquisition of PA was frequently followed by the development of an exacerbation and that approximately one third of PA strains demonstrated persistence, irrespective of the development of an immunological response mediated by antibodies.…”
Section: Introductionmentioning
confidence: 98%